News consumption patterns during the coronavirus pandemic across time and devices: The Cyprus case - Spyridou, Lia Paschalia; Danezis, Christos (My University, 2021)
The corona virus pandemic sparked a renewed interest in news consumption patterns. When major crises occur, people experience an increasing need for information and sense-making; given the extraordinary impact of this health crisis on people’s social and work life, relevant work support a ‘rally around the news’ effect, news fatigue and news avoidance, doomscrolling and a trend toward mainstream and trusted news outlets. This study explored how the corona virus pandemic shaped news consumption patterns in Cyprus. The results show that news use hit record levels at the onset of the crisis, followed by corona news fatigue in the following months. Increased news consumption levels and greater engagement with the news were recorded again in the last couple of months of 2020 when the second wave of the pandemic hit Cyprus. Direct traffic to widely used and trusted sources doubled while a crisis boosting effect on mobile access to the detriment of computers was recorded
Keywords: Corona virus; Consumption patterns